(untitled) (IAHS Medical Journal, 2025)
Background: The increasing prevalence of Extended-Spectrum Beta-Lactamase (ESBL)-producing pathogens is a significant concern in clinical microbiology, as these organisms resist a wide range of beta-lactam antibiotics, complicating treatment strategies. This study aimed to characterize ESBL-producing Klebsiella spp. Escherichia coli and Staphylococcus aureus isolated from clinical samples, including urine, wound swabs, sputum, and vaginal swabs. Materials and methods: A total of 74 clinical samples were analyzed, comprising 51 urine, 11 wound swab, 4 sputum and 8 vaginal swab samples collected from patients presenting with symptoms indicative of infections between June 2024 and September 2024. Bacterial isolates were identified using standard microbiological techniques and antimicrobial susceptibility testing was performed using the disk diffusion method. ESBL production was detected using the phenotypic confirmatory test. Results: Among the isolated pathogens, E. coli was the most prevalent, accounting for 49.0% of all samples, followed by Klebsiella spp. (36.4%) Staphylococcus aureus (9.1%) Pseudomonas aeruginosa (4.5%) and Proteus mirabilis (1.0%). The prevalence of ESBL production was high amongKlebsiella spp. (75%) and E. coli (72%) particularly in urine and wound isolates. Resistance rates to commonly used antibiotics were notably high, with E. coli showing 88% resistance to ampicillin, 76% to ciprofloxacin, and 75% to ceftriaxone. However, carbapenems remained effectivewith a low resistance rate of approximately 4%. Conclusions: The study highlighted the alarming prevalence of ESBL-producing E. coli and Klebsiella spp. with significant resistance to beta-lactams and fluoroquinolones. These findings underscore the need for stringent antibiotic stewardship, infection control measures and the use of alternative antibiotics like carbapenems for treating infections caused by multidrug-resistant organisms. Continued surveillance and molecular analysis are essential to track the spread of resistant pathogens and guide clinical treatment. IAHS Medical Journal Vol 7(2), December 2024; 19-24